2010
DOI: 10.1186/1471-2164-11-426
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variation at leptin receptor gene locus associated with metabolic traits and the risk of type 2 diabetes mellitus

Abstract: BackgroundRecent efforts have been made to link complex human traits and disease susceptibility to DNA copy numbers. The leptin receptor (LEPR) has been implicated in obesity and diabetes. Mutations and genetic variations of LEPR gene have been discovered in rodents and humans. However, the association of DNA copy number variations at the LEPR gene locus with human complex diseases has not been reported. In an attempt to study DNA copy number variations associated with metabolic traits and type 2 diabetes mell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 39 publications
1
31
1
1
Order By: Relevance
“…In a recent study, the association of the LEPR gene locus encompassing B200 kb on chromosome 1 was studied in the Korean population using the genome-wide SNP array data and it was found that CNV at the LEPR gene locus is significantly associated with metabolic traits and the risk to type 2 diabetes mellitus. 55 Overweight and obesity People with body mass index of 25 kg m À2 are considered overweight and those with body mass index of 30 kg m À2 are considered obese. As per one estimate 66% of the US population is overweight and among them about 30% are obese.…”
Section: Cnv and Susceptibility To Other Common Disorders Hiv/aids Sumentioning
confidence: 99%
“…In a recent study, the association of the LEPR gene locus encompassing B200 kb on chromosome 1 was studied in the Korean population using the genome-wide SNP array data and it was found that CNV at the LEPR gene locus is significantly associated with metabolic traits and the risk to type 2 diabetes mellitus. 55 Overweight and obesity People with body mass index of 25 kg m À2 are considered overweight and those with body mass index of 30 kg m À2 are considered obese. As per one estimate 66% of the US population is overweight and among them about 30% are obese.…”
Section: Cnv and Susceptibility To Other Common Disorders Hiv/aids Sumentioning
confidence: 99%
“…For example, a DNA copy number variation at the leptin receptor (LEPR) gene locus is associated with metabolic syndrome-related traits and risk of T2D. Lower LEPR copy numbers related to higher fasting glucose; and LEPR expression in lymphoblastoid cell lines correlated with the number of CNVs [48]. However, a role for common CNVs in the risk of T2D remains unclear.…”
Section: The "Missing Heritability" In Common Type 2 Diabetesmentioning
confidence: 99%
“…Additionally, leptin and its receptor inhibit insulin secretion by pancreatic b-cells. 22 Homozygous autosomal mutations in the leptin receptor gene (LEPR) in mice lead to obesity and insulin resistance, which can be reversed by the introduction of a neuron-specific LEPR-B transgene. 23 In agreement with these findings, common genetic variants at LEPR, located in chromosomal region 1p31, have been associated with obesity, 24 insulin resistance, T2DM 25 and variations in leptin levels 26,27 in different populations.…”
Section: Introductionmentioning
confidence: 99%